2022
DOI: 10.3389/fpubh.2021.734370
|View full text |Cite
|
Sign up to set email alerts
|

No Alteration Between Intrinsic Connectivity Networks by a Pilot Study on Localized Exposure to the Fourth-Generation Wireless Communication Signals

Abstract: Neurophysiological effect of human exposure to radiofrequency signals has attracted considerable attention, which was claimed to have an association with a series of clinical symptoms. A few investigations have been conducted on alteration of brain functions, yet no known research focused on intrinsic connectivity networks, an attribute that may relate to some behavioral functions. To investigate the exposure effect on functional connectivity between intrinsic connectivity networks, we conducted experiments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Evidence from previous studies indicates that exposure to EMR in experimental animals can cause changes in their behaviors, such as EMR (1.8 GHz), which is associated with anxiety-like and depressionlike behaviors in mice (Gupta et al 2019;. Yang et al (2022) found that there was no significant difference in static or dynamic functional network connectivity in both real and sham exposure conditions and noted that the impact of short-term electromagnetic exposure was undetected at the ICNs level. These changes depend largely on the duration, frequency, and intensity of EMR exposure.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Evidence from previous studies indicates that exposure to EMR in experimental animals can cause changes in their behaviors, such as EMR (1.8 GHz), which is associated with anxiety-like and depressionlike behaviors in mice (Gupta et al 2019;. Yang et al (2022) found that there was no significant difference in static or dynamic functional network connectivity in both real and sham exposure conditions and noted that the impact of short-term electromagnetic exposure was undetected at the ICNs level. These changes depend largely on the duration, frequency, and intensity of EMR exposure.…”
Section: Introductionmentioning
confidence: 91%
“…Yang et al. (2022) found that there was no significant difference in static or dynamic functional network connectivity in both real and sham exposure conditions and noted that the impact of short‐term electromagnetic exposure was undetected at the ICNs level. These changes depend largely on the duration, frequency, and intensity of EMR exposure.…”
Section: Introductionmentioning
confidence: 99%